Cooking with Fresh Herbs - Emily Minton; Martha Maddox (EDIS)
People worldwide are becoming more adventurous when cooking with fresh herbs. If you are just starting to use fresh herbs in your cooking or need a refresher, these tips for washing, storing, and cooking with herbs will lead you in the right direction. This revised 8-page fact sheet discusses the history of herbs, how to buy them fresh, how to wash and store them, dried herb blends, common herb and food combinations, and several recipes using herbs. Written by Emily Minton and Martha Maddox, and published by the Department of Family, Youth, and Community Sciences, October 2015. (Photo credit: LiliGraphie/iStock/Thinkstock.com)